Impact of the Global Financial Crisis in Rural China : Gender, Off-farm Employment, and Wages - Zhi, Huayong; Huang, Zhurong; Huang, Jikun; Rozelle, Scott D.; Mason, Andrew D. (Taylor and Francis, 2013)
This contribution documents the effect of the global financial crisis on women's off-farm employment in China's rural labor force. It begins by comparing the difference between the actual off-farm employment rate and the off-farm employment rate under the assumption of “business as usual” (BAU – a counterfactual of what off-farm employment would have been in the absence of the crisis). The study also examines how the impact of the financial crisis hit different segments of the rural off-farm labor market. Using a primary dataset, the study found that the global financial crisis affected women workers. By April 2009, there was a 5.3 percentage point difference between off-farm employment under BAU and actual off-farm employment for women, and the monthly wages of women declined. Most of this impact affected migrant wage earners; however, the impact did not fall disproportionately on women. The recovery of women's employment was as fast as that of men's employment.